Optimizing Anesthetic Selection in Transcatheter Aortic Valve Replacement: Striking a Delicate Balance between Efficacy and Minimal Intervention - Kahtan Fadah; Seyed Khalafi; Miller Corey; Jose Sotelo; Ahmed Farag; Tariq Siddiqui; Mehran Abolbashari (Cardiology Research and Practice)
Patients with severe calcific native aortic valve stenosis (AS) who require valve replacement have two options, surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR). TAVR was approved in late 2011 for extremely high-risk patients and was subsequently approved for high-risk (2012), intermediate-risk (2016), and low-risk (2019) patients. In 2019, TAVR procedures surpassed SAVR procedures for the first time in the United States. The approach to anesthesia for this procedure has also evolved. Initially, general anesthesia (GA) was preferred, but currently, conscious sedation (CS) is favored. This review aims to clarify the indications and contraindications for both approaches, as well as the advantages of one approach over the other. Recent studies show that conscious sedation has better outcomes in terms of all-cause mortality, procedure complications such as stroke, myocardial infarction, infection requiring antibiotics, acute kidney injury, and the need for inotropes or vasopressors.